ASAS FREIES ERMESSEN DAN ASPEK PERPAJAKAN LEASING MENURUT KEPUTUSAN MENTERI KEUANGAN NO. 1169/KMK.01/1991 TENTANG KEGIATAN SEWA GUNA USAHA (LEASING) - Syofyan, Syofrin (Faculty of Law, Parahyangan Catholic University, 2017)
This article discusses the government’s role in granting tax incentives in support of the leasing business which in itself already functions as a financing instrument. The author purports to show how the government’s (the state administration’s) freedom in making policy rules based on the principle of freies ermessen is realized in the economic (tax) sector. The policy rules being discussed is the Ministry of Finance’ Decree no. 1169/KMK.01/1991 re. Leasing.